2014
DOI: 10.1021/es503659w
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolomics Revealed Arsenic Internal Dose-Related Metabolic Alterations: A Proof-of-Concept Study in a Chinese Male Cohort

Abstract: Urinary biomonitoring provides the most accurate arsenic exposure assessment; however, to improve the risk assessment, arsenic-related metabolic biomarkers are required to understand the internal processes that may be perturbed, which may, in turn, link the exposure to a specific health outcome. This study aimed to investigate arsenic-related urinary metabolome changes and identify dose-dependent metabolic biomarkers as a proof-of-concept of the information that could be obtained by combining metabolomics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 61 publications
5
46
0
Order By: Relevance
“…Similarly, Emory University’s NIEHS-funded Human Exposome Research Center: Understanding Lifetime Exposures (HERCULES) has developed infrastructure that has supported several environmental health studies using hybrid biomonitoring approaches (Go et al 2014, 2015; Jones 2016; Zhang et al 2014). HELIX also uses a hybrid approach for data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Emory University’s NIEHS-funded Human Exposome Research Center: Understanding Lifetime Exposures (HERCULES) has developed infrastructure that has supported several environmental health studies using hybrid biomonitoring approaches (Go et al 2014, 2015; Jones 2016; Zhang et al 2014). HELIX also uses a hybrid approach for data collection.…”
Section: Discussionmentioning
confidence: 99%
“…A metabolomic study carried out in the general Chinese population identified several potential biomarkers of iAs exposure in urine (Zhang et al , 2014). Similarly, our recently published metabolomic analyses of urine and plasma from residents of Chihuahua, Mexico found 132 metabolites that were altered in iAs-exposed individuals (Martin et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Interaction between alcohol use and arsenic exposure has been studied among others by Bae et al (2013), Wadhwa et al (2013), and Zhang et al (2014). To the best of our knowledge, we do not know of a study in general U.S. population that has considered the interacting effect of arsenic exposure with smoking, alcohol, and caffeine consumption.…”
Section: Introductionmentioning
confidence: 99%